2014
DOI: 10.1002/maco.201407988
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion resistance of titanium dioxide anodic coatings on Ti–6Al–4V

Abstract: The Ti–6Al–4V alloy is used for biomedical implants due to its corrosion resistance and biocompatibility, associated with the spontaneous formation of TiO2 oxide. However, the native film may be flawed and after some time of implantation in the body it may release metal ions. Oxides of higher thickness than naturally grown can be produced by anodic oxidation. The objective of this study was to evaluate the corrosion resistance of anodic TiO2 coatings, evaluating the influence of the thickness and crystalline s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 35 publications
(43 reference statements)
0
11
0
Order By: Relevance
“…The presence of different time constants included in the equivalent circuit indicated that the formed films on the surface of the alloys were associated with a complex structure that consists of two layers, one is inner and the other is outer [37,38]. These two layers result from the dominant impedance at the high frequency region for the inner layer, while the impedance at the low frequency region is dominated by the outer layer, which is porous [37,38]. The Nyquist spectra of Figure 1, which were obtained after 1 h exposure in 3.5% NaCl solutions for the different alloys, depicted the same behavior with which the values of Z and Z" increased linearly.…”
Section: Eis Measurementsmentioning
confidence: 99%
See 3 more Smart Citations
“…The presence of different time constants included in the equivalent circuit indicated that the formed films on the surface of the alloys were associated with a complex structure that consists of two layers, one is inner and the other is outer [37,38]. These two layers result from the dominant impedance at the high frequency region for the inner layer, while the impedance at the low frequency region is dominated by the outer layer, which is porous [37,38]. The Nyquist spectra of Figure 1, which were obtained after 1 h exposure in 3.5% NaCl solutions for the different alloys, depicted the same behavior with which the values of Z and Z" increased linearly.…”
Section: Eis Measurementsmentioning
confidence: 99%
“…According to the values of polarization resistances listed in Table 2, the increase of resistance was directly proportional to the values of R P1 and R P2 (total R P = R P1 + R P2 ). The presence of different time constants included in the equivalent circuit indicated that the formed films on the surface of the alloys were associated with a Metals 2020, 10, 264 4 of 16 complex structure that consists of two layers, one is inner and the other is outer [37,38]. These two layers result from the dominant impedance at the high frequency region for the inner layer, while the impedance at the low frequency region is dominated by the outer layer, which is porous [37,38].…”
Section: Eis Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…For TiAlV6‐4, there exists a high number of publications on the corrosion behavior in various media, due to the widespread technical use of this alloy. In comparison, less information about the growth mechanism of passivating anodic oxide films are available.…”
Section: Introductionmentioning
confidence: 99%